Respostas

2013-05-26T03:03:33-03:00

(1-m)x-10y+3=0
10y= 1-mx + 3
y=(1-m)x + 3
         10

coeficiente angular : 1-m

                                        10
coeficiente linear : 3

                                 10

(m+2)x+4y-11m-18
4y= -(m+2)x+11m+18
y= (-m-2)x+11m+18
                   4

angular: -m-2

                    4
linear: 11m+18

                  4


concorrente: angular=angular  linear= linear

1-m=-m-2

10         4

 

4*(1-m)=10*(m-2)

4-4m=10m-20

-4m-10m=-20-4

-14m=-24 *(-1)

14m=24

m=24  simplificando:  12

      14                               7

 

agora só falta linear ser igual linear.

 

 3=11m+18

10         4

 

12=10*(11m+18)

12=110m+180

180-12=110m

110m=168

m=168  = 84

      110     55

 

Abraços.

 

11 3 11